Catecholamine concentrations in duck eggs are impacted by hen exposure to heat stress - Lyte, Joshua M.; Lyte, Mark; Daniels, Karrie M.; Oluwagbenga, Esther M.; Fraley, Gregory S. (Frontiers in Physiology, 2023)
Rapid ‘fight-or-flight’ responses to stress are largely orchestrated by the catecholamines. Moreover, catecholamines and catecholamine precursors are widely recognized to act as interkingdom signaling molecules among host and microbiota, as well as to serve as chemotactic signals for bacterial foodborne pathogens. While albumen and yolk concentrations of glucocorticoids have received extensive attention as non-invasive indicators of hen response to stress, little is known regarding the impact of the hen’s stress response on in ovo catecholamine and catecholamine precursor concentrations. The aim of the present study was to determine norepinephrine and L-dopa concentrations in albumen and yolk of eggs laid by hens maintained under normal or heat stress conditions. Norepinephrine and L-dopa concentrations were also measured in oviductal tissue. Breeder ducks (~35 wks/age) were kept under normal (22oC) conditions or subjected to cyclical heat stress (35oC day/29.5oC night) for three weeks. Eggs (n=12 per timepoint/group) were collected on a weekly basis. Hens were sacrificed at baseline or after 3 weeks of heat stress for oviductal tissue collection. Albumen, yolk, and oviduct concentrations of norepinephrine and L-dopa were determined using ultra high-performance liquid chromatography with electrochemical detection. Norepinephrine and L-dopa were detected in oviductal tissue as well as egg albumen and yolk. Norepinephrine concentrations were elevated (p<0.05) in the yolk of eggs laid by the heat stress group compared to those of the control group. Norepinephrine concentrations in albumen were elevated (p<0.05) in the heat stress group compared to control group at week 2. L-dopa concentrations were not significantly affected (p>0.05) by heat stress in albumen, yolk, or oviductal tissue. Together, the present study provides the first evidence of the stress neurohormone, norepinephrine, in duck eggs and identifies that hen exposure to heat stress can affect in ovo norepinephrine concentrations. These data highlight the potential utility of in ovo catecholamine concentrations as non-invasive measures of the hen’s response to stress, as well as warrants future research into whether hen deposition of stress-related neurochemicals into the egg could serve as a chemotactic signal in the vertical transmission of foodborne pathogens.